Loss of Vascular Myogenic Tone in miR-143/145 Knockout Mice Is Associated With Hypertension-Induced Vascular Lesions in Small Mesenteric Arteries. Issue 2 (February 2018) - Holmberg, Johan; Bhattachariya, Anirban; Alajbegovic, Azra; Rippe, Catarina; Ekman, Mari; Dahan, Diana; Hien, Tran Thi; Boettger, Thomas; Braun, Thomas; Swärd, Karl; Hellstrand, Per; Albinsson, Sebastian
Abstract : Objective—: Pressure-induced myogenic tone is involved in autoregulation of local blood flow and confers protection against excessive pressure levels in small arteries and capillaries. Myogenic tone is dependent on smooth muscle microRNAs (miRNAs), but the identity of these miRNAs is unclear. Furthermore, the consequences of altered myogenic tone for hypertension-induced damage to small arteries are not well understood. Approach and Results—: The importance of smooth muscle–enriched microRNAs, miR-143/145, for myogenic tone was evaluated in miR-143/145 knockout mice. Furthermore, hypertension-induced vascular injury was evaluated in mesenteric arteries in vivo after angiotensin II infusion. Myogenic tone was abolished in miR-143/145 knockout mesenteric arteries, whereas contraction in response to calyculin A and potassium chloride was reduced by ≈30%. Furthermore, myogenic responsiveness was potentiated by angiotensin II in wild-type but not in knockout mice. Angiotensin II administration in vivo elevated systemic blood pressure in both genotypes. Hypertensive knockout mice developed severe vascular lesions characterized by vascular inflammation, adventitial fibrosis, and neointimal hyperplasia in small mesenteric arteries. This was associated with depolymerization of actin filaments and fragmentation of the elastic laminae at the sites of vascular lesions. Conclusions—: This study demonstrates that miR-143/145 expression is essential for myogenic responsiveness. During hypertension, loss of myogenic tone results in potentially damaging levels of mechanical stress and detrimental effects on small arteries. The results presented herein provide novel insights into the pathogenesis of vascular disease and emphasize the importance of controlling mechanical factors to maintain structural integrity of the vascular wall. Abstract : Supplemental Digital Content is available in the text.